2014
DOI: 10.1080/01634372.2013.847885
|View full text |Cite
|
Sign up to set email alerts
|

Transitions in Caregiving: Evaluating a Person-Centered Approach to Supporting Family Caregivers in the Community

Abstract: Caregivers of older adults provide a wide range of informal supports and services that enable older adults to continue living in the community. This study describes the use of a multicomponent intervention combined with a person-centered approach to assist caregivers of older adults in the community. Four hundred and eighteen caregiver and care recipient dyads participated in this study and their outcomes related to burden, depression, well-being, and care recipient functional status were evaluated. The findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…The resulting network analysis and change stories offer a rich illustration of how an evaluation methodology can capture more elusive measures such as the impact of spiritual support and religiosity on caregivers. Lastly, Sundar et al (2014) evaluate a multicomponent intervention for caregivers and find that a person-centered approach is key to address differences in the experience of burden by adult children and spousal caregivers.…”
Section: Collaborative Network and Capacitymentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting network analysis and change stories offer a rich illustration of how an evaluation methodology can capture more elusive measures such as the impact of spiritual support and religiosity on caregivers. Lastly, Sundar et al (2014) evaluate a multicomponent intervention for caregivers and find that a person-centered approach is key to address differences in the experience of burden by adult children and spousal caregivers.…”
Section: Collaborative Network and Capacitymentioning
confidence: 99%
“…to caregivers. Six articles in this special issue were funded through the Weinberg Caregiver initiative (Black, 2014;Iris, Berman, & Stein, 2014;Kally, Cherry, Howland, & Villarruel, 2014;Kally, Cote, et al, 2014;Rosenthal Gelman, Sokoloff, Graziani, Arias, & Peralta, 2014;Sundar, Fox, & Phillips, 2014). Together, the articles in this special issue provide a foundation for continuing to create services and support for caregivers.…”
mentioning
confidence: 94%
“…In 1995, Aneshensel and associates further noted that “the conceptual framework of the stress process is particularly useful in capturing the dynamic features of problematic life experience, caregiving being an excellent case in point” (9, p 35). Common sources of stress associated with caregiving include changes in role function, additional financial responsibilities, assisting with activities of daily living, and dealing with potential behavioral problems of care recipients ( 10 ). Caregiving may create a context in which caregivers experience stress and burden, but methods of coping among caregivers vary considerably.…”
Section: Caregiver Burden Quality Improvement Projectmentioning
confidence: 99%
“…For older adults with chronic illness, such as diabetes, disease management is rarely limited to only the individual with the disease who often also has co-morbid conditions. In fact, it is estimated that families provide 75% to 80% of long-term care in the community (Ankuda & Levine, 2016; Levine, Halper, Peist, & Gould, 2010; Sundar, Fox, & Phillips, 2014). This is supported by Wolff and Boyd (2015) who suggested that based on secondary analysis of the National Health and Aging Trends Study, one third of all U.S. adults aged 65 or older comanage health care activities with family or close friends.…”
Section: Introductionmentioning
confidence: 99%